The state bank for the development of agriculture on the example of the Landwirtschaftliche Rentenbank in Germany - Poppe, Anna-Lena (Przegląd Prawa Rolnego, 2023)
This article looks at state banks for agricultural development in Germany and Poland. While in Germany a special credit institution in the form of the Landwirtschaftliche Rentenbank has been created, in Poland a guarantee fund has been established within the structures of the state bank for development. The study has confirmed that state support extended in the form of agricultural credit, whether through the creation of a special state bank supporting and promoting agriculture or through the establishment of an agricultural guarantee fund, enables agricultural enterprises in Germany and Poland to cover their credit needs, secure liquidity and, consequently, maintain their business. However, especially in the context of the environmental challenges and the digitalisation of agriculture, there is no sign that borrowing needs of the agricultural sector will be declining, and therefore state support of agricultural credit will continue to play an important role.